2022
DOI: 10.1523/jneurosci.0836-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Manipulations of Physiological Arousal and Sleep-Like Slow Waves Modulate Sustained Attention

Abstract: Sustained attention describes our ability to keep a constant focus on a given task. This ability is modulated by our physiological state of arousal. Although lapses of sustained attention have been linked with dysregulations of arousal, the underlying physiological mechanisms remain unclear. An emerging body of work proposes that the intrusion during wakefulness of sleeplike slow waves, a marker of the transition toward sleep, could mechanistically account for attentional lapses. This study aimed to expose, vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Other regions that were found to have higher synchronization in the high-high FSA group compared to the low-low and low-high FSA groups include the temporal parietal junction, frontal eye fields, superior parietal lobule, intraparietal sulcus, and ventral premotor cortex, which comprise the dorsal attention network (DAN; Spreng et al, 2017). The DAN is a bilateral network that focuses human attention (Farrany & Uddin, 2015), and sustained attention is modulated by physiological states of arousal (Pinggal et al, 2022). Further, higher levels of attention have been shown to enhance neural synchrony during narrative processing (Jääskeläinen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other regions that were found to have higher synchronization in the high-high FSA group compared to the low-low and low-high FSA groups include the temporal parietal junction, frontal eye fields, superior parietal lobule, intraparietal sulcus, and ventral premotor cortex, which comprise the dorsal attention network (DAN; Spreng et al, 2017). The DAN is a bilateral network that focuses human attention (Farrany & Uddin, 2015), and sustained attention is modulated by physiological states of arousal (Pinggal et al, 2022). Further, higher levels of attention have been shown to enhance neural synchrony during narrative processing (Jääskeläinen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cortical arousal is self-generated through the reticulate formation and propagated through dorsal thalamic and ventral subthalamic pathways 21 , and can be indexed by the alpha, theta, and delta EEG bands during wakefulness 22,23 . Lower levels of cortical arousal in the form of slow waves have been associated with an increased number of missed stimuli in behavioral tasks 11,23 and decreased thought intensity 24 . Also, lower levels of arousal indexed by pupil size have been correlated with a higher probability of MB reports in sustained attention tasks 11,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Early on, Lacey viewed arousal in terms of behavioral arousal (indicated by a responding organism, like restlessness and crying), cortical arousal (evidenced by desynchronized fast oscillatory activity), and autonomic arousal (indicated by changes in bodily functions) 20 . Cortical arousal is self-generated through the reticulate formation and propagated through dorsal thalamic and ventral subthalamic pathways 21 , and can be indexed by the alpha, theta, and delta EEG bands during wakefulness 22,23 . Lower levels of cortical arousal in the form of slow waves have been associated with an increased number of missed stimuli in behavioral tasks 11,23 and decreased thought intensity 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The monoamine systems have a great impact on memory, cognition, and emotions [ 11 ]. Studies with administration of monoamine reuptake inhibitors to healthy men showed that methylphenidate, which elevates DA and NE content in both the cortex and subcortical structures, increased the number of correct responses during the visual task, while atomoxetine, which mainly affects the frontal cortex, led to more impulsive reactions, and citalopram increased the number of missed stimuli [ 12 ]. The monoamines are involved in the implementation of impulsive and aggressive behavior, emotional instability, inhibitory control of these behavioral patterns, and a number of other symptoms of disorders associated with traumatic experiences [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%